Alumina-Forming Austenitic (AFA) steels and aluminium-based coating on 15-15 Ti steel to limit mechanical damage in presence of liquid lead-bismuth eutectic and liquid lead - Proriol Serre Ingrid (EDP Sciences, 2021)
To limit corrosion of the steels in contact with liquid metal (Pb or Pb-Bi), both different solutions based on the presence of alumina at the surface of the steels were selected: 2 Alumina-Forming Austenitic (AFA) steels and the 15-15 Ti steel coated by alumina layer. These technical options to mitigate corrosion by lead or Pb-Bi were investigated in terms of mechanical performances in liquid lead or liquid Pb-Bi. So the liquid metal embrittlement (LME) sensitivity of the different materials selected for their good corrosion resistance was evaluated by tensile tests or small punch tests carried out in presence of liquid metal, and by post-mortem analysis of the cracking and of the fracture surfaces. No LME sensitivity for the tested conditions has been observed for the Al2O3 coated 15-15Ti steel and for the two AFA steels (16Ni-14Cr-2.5Al-2.5Mn-1Nb), one without and one with 2% wt.% W and 0.02% wt.% Y in their as received state. But a 650 °C thermal aging promotes modifications of the microstructure specially precipitations and then LME sensitivity of the AFA steels, according the nature of the precipitation.